2022
DOI: 10.31557/apjcp.2022.23.2.409
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Gastrointestinal Cancers: Results from National Cancer Registry Programme, India

Abstract: Purpose: This study aims to determine the incidence, histology, clinical extent of disease, and trends of gastrointestinal (GI) cancers in India. Methods: GI cancer cases diagnosed between 2012-2016 from 28 Population-Based Cancer Registries and 58 Hospital Based Cancer Registries under the National Cancer Registry Programme were included. Crude incidence rate and age-standardized incidence rates (AARs) were calculated. Joinpoint regression program, 4.0.1 was used for trend analysis for data from 1982 to 2016,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Higher prevalence of obesity, inadequate physical activity, salt and red meat consumption, diabetes, and low consumption of fibre among urban residents could partly decipher the higher incidence rates in the urban population [ 49 ]. Our findings are in line with studies from India that have reported a rising trend in registries established in metropolitan regions (predominantly urban population) such as Delhi, Chennai, Mumbai, and Banglore [ 50 ], and studies from China [ 14 , 51 ]. In contrast, studies from the US show a rural preponderance for colon cancer, which has been attributed to higher red meat consumption, obesity, a lack of physical activity, and lower cancer screening adherence in their rural populations [ 34 , 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…Higher prevalence of obesity, inadequate physical activity, salt and red meat consumption, diabetes, and low consumption of fibre among urban residents could partly decipher the higher incidence rates in the urban population [ 49 ]. Our findings are in line with studies from India that have reported a rising trend in registries established in metropolitan regions (predominantly urban population) such as Delhi, Chennai, Mumbai, and Banglore [ 50 ], and studies from China [ 14 , 51 ]. In contrast, studies from the US show a rural preponderance for colon cancer, which has been attributed to higher red meat consumption, obesity, a lack of physical activity, and lower cancer screening adherence in their rural populations [ 34 , 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, all gallbladder specimens should be examined histopathologically after cholecystectomy performed for benign gallbladder disease. The most common morphology has been reported as adenocarcinoma in biliary tract and pancreatic malignancies [ 16 , 23 ] similar to the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Shakuntala et al in their study describing the GI cancers in India also concluded that the most common site for GI cancer in India is oesophagus followed by stomach and rectum. 7 A study based on hospital based cancer registry in Kashmir valley by Qurieshi et al reported stomach cancer to be most common followed by colorectal and then cancer oesophagus. 20 The difference may be on account of different study profile as our participants included only subjects coming for follow up and not only incident cases as was the case with the other study.…”
Section: Discussionmentioning
confidence: 99%
“…4 These figures have not included cancers of oral cavity/lips which are one of the most common causes in India, particularly in males. [5][6][7] This data suggests that GI cancers are more likely to cause deaths as these contribute to almost 1/4 th of all cancer deaths in the country. 8 The most common GI cancers are CRC, stomach cancer, EC, liver cancer, gallbladder cancer, and PC.…”
Section: Introductionmentioning
confidence: 99%